(3GdJMbjb hGdJfbjQajeG jJYdb HGdebGOjQs - (3GdMdj, GdLfGLj, GdfLaj, ef Bd cGTa GdZWGA, LYaQ Hf NVQ Hf TdGd, J (B1227 (3g`s ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg HGQj GdfSe (B... (3Ef GdCdaGX GdeJQOOI aj cdGe GdeJTQYI eeG jJYdb HGdhRf cKjQI efgG GdOQge hGdOjfGQ hGdeKbGd hGdQWd hGdeO hGdUGYs
(3BNQgG (B:s
(3BNQgG(B: (3hGdUGY JSYI CQWGd acCf YHGQI (B.. (3Cda hSHY eFI QWd cCf HGdYWGQej NeSG hYTQjf hRfI hefjf hJSY ChGb hHGdHbGdj JSYI YTQ hRfI hKdGKI LhGQjc hKdGKI CQHGYj ChbjI agPG BNQ eG CQOfG JMQjQg aj gPg GdQSGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 124s
(3GdPQjYI, L (B3: 266s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis